TOLSYASUPI-EduMed: Development of Educational Media Using the Problem-Posing Learning Model for Basic Programming Subjects - Syahidi, Aulia Akhrian; Tolle, Herman; Supianto, Ahmad Afif; Hirashima, Tsukasa (Journal of Information Technology and Computer Science, 2019)
The importance of expertise in the field of programming today makesVocational High Schools as early as a possible incorporate curriculum that canlearn skills in programming, which is then called basic programming subjects.These subjects are the initial foundation, to study other productive subjects thatmust be studied by students in the field of ICT expertise. However, in reality,students tend to dislike these subjects because they feel difficulties inunderstanding and learning them. Therefore, we try to present a solution toovercome this problem by developing basic programming educational media,especially in the material of branching control structures by embedding thesyntax of problem-posing learning models in the type of open-posing into theinteraction flow. This educational media is called TOLSYASUPI-EduMed. Theresearch and development method (R&D) was used as the main method in thisstudy. The model for system development uses ADDIE by adapting the R&Dmethod. A/B testing methods are used to validate the initial selection ofeducational media design. The form of design until the development stage isvalidated by media and material experts as much as 3 iterations, to ensure thatthe educational media can look for effects on the effectiveness of learning. Atotal of 36 students were involved in the use of this educational media.Evaluation of the use of educational media to determine aspects of satisfactionand usability using the Computer System Usability Questionnaire (CSUQ)method. The results of the study stated that 90.9% of experts agreed that VeryStrong to choose design B to continue at the advanced design, development,and implementation stages. The results of the validation of media and materialexperts state that it is feasible to use. Based on functional requirementsspecifications, all features function properly, and non-functionally 94.49% withpredicates Very Strong that end-users (students) are satisfied and feel theusefulness of this TOLSYASUPI-EduMed.